Luteolin improves mitochondrial dynamics and function in ulcerative colitis via the miR-195-5p/Notch signalling pathway - Moxixuan Liu; Yuge Wang; Zhao Liu; Senxia Liu; Qian Yang; Bolin Li (Journal of Functional Foods)
Luteolin (Lut), a plant extract widely found in nature, has demonstrated extensive therapeutic potential across various diseases. In this study, Lut treatment mitigated dextran sulphate sodium (DSS)-induced intestinal mucosal injury in a mouse model of ulcerative colitis (UC), which is associated with the activation of the Notch signalling pathway. Notably, colonic tissues exhibited reduced expression of Notch1, Notch2, RBPJ, MAML1, Hes1, Jagged1, and DLL4 following Lut administration. Additionally, our findings corroborate the hypothesis that miR-195-5p plays a critical role as a mediator in the negative feedback regulation of the Notch signalling pathway. In UC mice, inhibition of mitochondrial respiration and decreased energy production were observed, but Lut treatment effectively enhanced the energy metabolism within colon tissues. Moreover, mitochondrial fission was elevated, and fusion was suppressed in the colons of UC mice. Lut administration significantly increased the expression of mitochondrial fusion factors MFN1 and MFN2, reduced the expression of mitochondrial fission factors Fis1 and Crmp1, and markedly improved mitochondrial morphology, change mitochondrial membrane potential. During the entire mice experiment, a dosage of 100 mg/kg/d of Lut demonstrated significant advantages over 50 mg/kg/d of Lut in the treatment of UC. Furthermore, in Caco-2 cells, Lut attenuated LPS-induced activation of the Notch signalling pathway, evidenced by the downregulation of Notch1, MAML1, Hes1, Jagged1, and DLL4. The inhibitory role of miR-195-5p on the Notch signalling pathway was further substantiated by miR-195-5p overexpression in Caco-2 cells. LPS treatment also induced increased mitochondrial fission and decreased fusion in Caco-2 cells, while Lut effectively restored the levels of mitochondrial fusion factors MFN1 and MFN2, lowered the levels of mitochondrial fission factors Fis1 and Crmp1, and improved mitochondrial viability. These results indicate that Lut may exert an inhibitory effect on the Notch signalling pathway via miR-195-5p, while its impact on mitochondrial dynamics and the preservation of mitochondrial morphology and function offers protection against UC-associated colonic damage and LPS-induced injury in Caco-2 cells.